PURIFICATION AND CHARACTERIZATION OF BACTERIOCIN FROM FERMENTED VEGETABLES - S. HEMALATHA,; K. LOGESHWARI, (International Journal of Pharma and Bio Sciences, 2015)
Bacillus sp., Leuconostoc mesenteroides, Vagococcus sp., and Pediococcus sp. were isolated from fermented vegetables. All the four isolates produced bacteriocin and they have showed antibacterial activity against E. coli, B. subtilis and K. pneumoniae. Bacteriocin was stable at various temperature and pH. But it was sensitive to enzymes such as α amylase, lipase and pepsin and also affected by high percentage of salt concentration. SDS-PAGE analysis have shown peptide < 35 KDa.